Effect of combustion-derived particles on genotoxicity and telomere length: A study on human cells and exposed populations. (1st April 2020) - Ma, Yanying; Bellini, Nicoletta; Scholten, Rebecca Harnung; Andersen, Maria Helena Guerra; Vogel, Ulla; Saber, Anne Thoustrup; Loft, Steffen; Møller, Peter; Roursgaard, Martin
Highlights: Particles were collected in diesel-powered trains and firefighter training location. Particles generated intracellular reactive oxygen species in A549 cells. Long-term exposure to particles promoted shortening in telomeres in A549 cells. Shorter telomeres were observed in mononuclear blood cells of particle-exposed humans. Abstract: Particulate matter (PM) from combustion processes has been associated with oxidative stress to DNA, whereas effects related to telomere dysfunction are less investigated. We collected air-borne PM from a passenger cabin of a diesel-propelled train and at a training facility for smoke diving exercises. Effects on oxidative stress biomarkers, genotoxicity measured by the comet assay and telomere length in PM-exposed A549 cells were compared with the genotoxicity and telomere length in peripheral blood mononuclear cells (PBMCs) from human volunteers exposed to the same aerosol source. Although elevated levels of DNA strand breaks and oxidatively damaged DNA in terms of Fpg-sensitive sites were observed in PBMCs from exposed humans, the PM collected at same locations did not cause genotoxicity in the comet assay in A549 cells. Nevertheless, A549 cells displayed telomere length shortening after four weeks exposure to PM. This is in line with slightly shorter telomere length in PBMCs from exposed humans, although it was not statistically significant. In conclusion, the results indicate that genotoxic potency measured by the comet assay of PM in A549 cells may not predict genotoxicity in exposed humans, whereas telomere length measurements may be a novel indicator of genotoxic stress in cell cultures and humans.